2017
DOI: 10.1016/j.jphotochem.2017.01.029
|View full text |Cite
|
Sign up to set email alerts
|

Increasing the efficiency of magnetic heterogeneous Fenton catalysts with a simple halogen visible lamp

Abstract: The effect of a simple visible halogen lamp was studied in the Fenton-type oxidation of three model aqueous pollutants differing in their structure and electrostatic charge, methylorange (MO), methylene blue (MB) and paranitrophenol (PNP), using maghemite nanoparticles (γ-Fe 2 O 3 NP), or maghemite/silica nanocomposite microspheres (γ-Fe 2 O 3 /SiO 2 MS) as heterogeneous catalysts. These materials, which were fully characterized, differ in size, morphology, porosity and microstructure, although their catalytic… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
5
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
4
3

Relationship

1
6

Authors

Journals

citations
Cited by 14 publications
(5 citation statements)
references
References 53 publications
0
5
0
Order By: Relevance
“…We also observed a low level of leaching and a good reusability for this catalyst, but relatively low activities, and moderate mineralization levels, were obtained in the absence of light [20,35]. However, we reported that the efficiency of this material can be improved through the use of visible light [34]. But photoactivation is not always practicable at a large scale, or when the effluent is characterized by a high level of turbidity or absorbance [36].…”
Section: Introductionmentioning
confidence: 82%
See 3 more Smart Citations
“…We also observed a low level of leaching and a good reusability for this catalyst, but relatively low activities, and moderate mineralization levels, were obtained in the absence of light [20,35]. However, we reported that the efficiency of this material can be improved through the use of visible light [34]. But photoactivation is not always practicable at a large scale, or when the effluent is characterized by a high level of turbidity or absorbance [36].…”
Section: Introductionmentioning
confidence: 82%
“…The γ-Fe 2 O 3 NPs used in this study were the same as those used in our previous papers [20,34,35]. The first step is the coprecipitation of Fe 2+ and Fe 3+ ions in order to get magnetite (Fe 3 O 4 ) NPs [37].…”
Section: Catalysts Preparation 211 Preparation Of the Maghemite Nanop...mentioning
confidence: 99%
See 2 more Smart Citations
“…are the major factors in the selection of the camera light source. The commonly used light sources are halogen lamps (fiber light sources), high frequency fluorescent lamps, and LED light sources (Ferroudj et al., 2017; X. Zhou et al., 2010). For example, Zhang et al.…”
Section: Odor Imaging Systemmentioning
confidence: 99%